High levels of genetic variability and population differentiation in Gressittacantha terranova (Collembola, Hexapoda) from Victoria Land, Antarctica - Fanciulli, Pietro Paolo; Summa, Domenico; Dallai, Romano; Frati, Francesco (Antarctic Science, 2001)
Allozyme electrophoresis was used to assess genetic variability and differentiation in 22 populations of Gressittacantha terranova Wise (Hexapoda, Collembola) from a coastal area of Victoria Land between the Mariner Glacier and the Nansen Ice Sheet. Allelic frequencies were determined at five enzyme loci: Phi, Pgm, Hk, Mpi and Mdh. Levels of variability, estimated as rates of heterozygosity, were higher than those calculated for the same loci in taxonomically related and non-related species of non-Antarctic Collembola. Thus, in spite of the ecological simplicity of Antarctic terrestrial ecosystems, G. terranova is characterized by high levels of genetic variability, and the 22 populations could be divided into three geogaphic groups, separated by the Aviator and Campbell glaciers. Genetic differentaton reflects the geographic arrangement of the populations, suggesting that the glaciers are effective barriers to gene flow, and that the patchy distribution of collembolan species in Antarctica has the potential to induce, in the long term, microspeciation processes. Interestingly, detectable genetic differentiation was observed between six populations collected at Edmonson Point, even though these are very close to each other, indicating the impact of geographic isolation even within short distances. The only exception to the congruence between genetic and geographic structuring was provided by the population of Apostrophe Island, for which a recent introduction with individuals coming from southern populations is suggested.